2021
DOI: 10.1002/jso.26374
|View full text |Cite
|
Sign up to set email alerts
|

Blood testis barrier revisited—Analysis of post‐chemotherapy germ cell tumor orchidectomy and retroperitoneal lymph node dissection specimens

Abstract: Objective To assess the response of chemotherapy on the primary tumor, compare it with the response in retroperitoneal disease, and study factors associated with pathological complete response. Methods We conducted a retrospective audit of all high inguinal orchidectomies (HIOs) performed after chemotherapy between 2012 and 2019 at a tertiary cancer center in India. Patient characteristics and histopathological response were extracted from electronic medical records, and predictors of testicular disease respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The barrier is strong enough to even limit the effect of chemotherapy, with most childhood leukemia relapses being in the testis. 55 The average concentration of cfDNA in patients with TGCT was measured at 10 ng/mL while healthy controls had 1 ng/mL, which showed discriminatory power. 40 However, multiple studies have shown that the concentration of cfDNA in the blood of healthy controls is highly variable and ranges from 0 to 100 ng/mL with the average value of 30 ng/mL, while in patients with cancer the range is 5–1000 ng/mL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The barrier is strong enough to even limit the effect of chemotherapy, with most childhood leukemia relapses being in the testis. 55 The average concentration of cfDNA in patients with TGCT was measured at 10 ng/mL while healthy controls had 1 ng/mL, which showed discriminatory power. 40 However, multiple studies have shown that the concentration of cfDNA in the blood of healthy controls is highly variable and ranges from 0 to 100 ng/mL with the average value of 30 ng/mL, while in patients with cancer the range is 5–1000 ng/mL.…”
Section: Discussionmentioning
confidence: 90%
“… 23 , 61 Everything from the time of day when sampling, the satiety and exertion level of the patient, the type of needle in blood drawing, the selection of blood tubes, sample transportation, the temperature, and time that takes from the blood to be processed, choice between blood serum and plasma, centrifugation protocols, storage of plasma or serum before cfDNA isolation, freeze-thawing of plasma or serum, HIL (hemolysis, icterus and lipemia) presence, choice of cfDNA isolation and quantification methods as well as cfDNA storage methods and duration has been shown to create variability in the final analysis results, especially with regards to cfDNA concentration and fragmentation. 23 , 62 66 This is both due to the effects of these variables on cfDNA degradation and isolation, but even more importantly, variations in sample processing can lead to genomic DNA contamination. 23 , 62 , 67 Even when certain procedures have become widely accepted or suggested, such as double-step centrifugation in blood plasma or serum preparation, minimizing the number of freeze-thawing events, usage of blood plasma and use of automated methods for cfDNA isolation the variations persist.…”
Section: Discussionmentioning
confidence: 99%